MOTIVASI BELAJAR SISWA DAN KETERLIBATAN SISWA DALAM PEMBELAJARAN DARING PENDIDIKAN JASMANI - Tatang Suryadin (JOURNAL RESPECS (Research Physical Education and Sports), 2022)
This research aims to find out students' learning motivation and student involvement in online learning of physical education to the Junior Highschool students at SMPN 1 Arjawinangun. This research is a survey study using a quantitative descriptive approach. The instruments in this study used anket, while the sampling technique was simple random sampling. With a sample number of 92 students. Analysis of the data used in this study is a quantitative descriptive analysis with percentages. The results of this study show the motivation of learning students in online learning of physical education in SMPN 1 Arjawinangun. In detail it shows the motivation for learning students in the high category with an average of 92 respondents of 94.43 (78.70%). Motivation to study students in online learning physical education which is very high thanks to 31 students (34%), high in number 60 students (65%), low in 1 student (1%) and very low in number of 0 students (0%). Whereas the results of research on student involvement in online learning of physical education in the high category, with an average of 92 respondents of 59.97 or (74.96%). Student involvement in online learning physical education which is very highly categorized by 15 students (16%), high in 75 students (82%), low in 2 students (2%) and very low in 0 students (0%).